Ischemic Heart Disease Modifies the Association of Atrial Fibrillation With Mortality in Heart Failure With Reduced Ejection Fraction. Issue 20 (16th October 2018) - Mercer, Ben N.; Koshy, Aaron; Drozd, Michael; Walker, Andrew M. N.; Patel, Peysh A.; Kearney, Lorraine; Gierula, John; Paton, Maria F.; Lowry, Judith E.; Kearney, Mark T.; Cubbon, Richard M.; Witte, Klaus K.
Abstract : Background: The CASTLE‐AF (Catheter Ablation versus Standard Conventional Therapy in Patients With Left Ventricular Dysfunction and Atrial Fibrillation) trial recently reported that catheter ablation of atrial fibrillation (AF) improves survival in heart failure (HF) with reduced ejection fraction (HFrEF). However, established AF was not associated with mortality in trials of contemporary HFrEF pharmacotherapies. We investigated whether HFrEF pathogenesis may influence the conclusions of studies evaluating the prognostic impact of AF. Methods and Results: Using a prospective cohort study of 791 patients with HFrEF, with AF determined using 24‐hour ambulatory ECG monitoring, univariable and multivariable Cox regression analyses were used to define the association between AF and mode‐specific mortality (mean follow‐up of 5.4 years). One‐year HF‐related hospitalization was assessed with binary logistic regression analysis. One‐year cardiac remodeling was assessed in a subgroup (n=378) using echocardiography. AF was present in 28.2% of patients, with 9.4% of these being paroxysmal. While AF was associated with increased risk of all‐cause mortality (hazard ratio, 1.27; 95% confidence interval 1.03–1.57), with diverging survival curves after 1 year of follow‐up, this association was lost in age‐sex–adjusted analyses. However, AF was associated with increased risk of age‐sex–adjusted all‐cause mortality in people with ischemic pathogenesis, with a statistically significant interaction between pathogenesis and AF. This was predominantly attributed to progressive HF deaths. After 1 year, HF hospitalization and cardiac remodeling were not associated with AF, even in people with ischemic pathogenesis. Conclusions: AF is associated with increased risk of death in HFrEF of ischemic pathogenesis, predominantly due to progressive HF deaths during long‐term follow‐up. HFrEF pathogenesis should be considered in trial design and interpretation.